(untitled) (Revista Apotheke, 2026)
Places destined for artistic creation, commonly, existences and projections converge; they allow us to see, as a sample space, facts and possibilities and, above all, they contain anxieties, desires and urgencies that cross and contaminate the artist’s thinking. In this sense, consisting of artistic propositions made during the years 2020 and 2021, a period in which, isolated, we survived the harshest days of the coronavirus pandemic, the present visual essay thinks of the domestic environment as a research laboratory, artistic processes as experiments, and the human body as an object of study and analysis. In this way, he presents a set of works that, guided by photographic practice and in dialogue with the imagetic universe of medical-laboratory sciences, drains anguish and reflections that arose in that context – in which the maintenance of life was conditioned to social isolation and human losses were transmuted into statistics, cold numbers almost detached from any trace of humanity; subjects transformed into objects. “body of studies, objects of analysis” registers, therefore, a cut of poetic investigation; samples of a practice associated with a specific time and place, a body and some fears.